The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3758/s13414-015-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Converging evidence that common timing processes underlie temporal-order and simultaneity judgments: a model-based analysis

Abstract: Perception of simultaneity and temporal order is studied with simultaneity judgment (SJ) and temporal-order judgment (TOJ) tasks. In the former, observers report whether presentation of two stimuli was subjectively simultaneous; in the latter, they report which stimulus was subjectively presented first. SJ and TOJ tasks typically give discrepant results, which has prompted the view that performance is mediated by different processes in each task. We looked at these discrepancies from a model that yields psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Moreover, any model will need to account for how information from different modalities is timed. Recent work directly comparing tasks, such as temporal order and simultaneity judgements, has shown that different patterns of data arise depending on what participants are asked to do [51], [52]. Multisensory studies of both rate and duration can, in tandem with a broad range of other tasks, help probe the plausibility of different models of temporal perception.…”
Section: Figurementioning
confidence: 99%
“…Moreover, any model will need to account for how information from different modalities is timed. Recent work directly comparing tasks, such as temporal order and simultaneity judgements, has shown that different patterns of data arise depending on what participants are asked to do [51], [52]. Multisensory studies of both rate and duration can, in tandem with a broad range of other tasks, help probe the plausibility of different models of temporal perception.…”
Section: Figurementioning
confidence: 99%
“…This type of data have been reported in a number of independent studies (e.g., Capa et al, 2014;Fujisaki & Nishida, 2009;Li & Cai, 2014;Linares & Holcombe, 2014;Matthews & Welch, 2015;Sanders et al, 2011;Schneider & Bavelier, 2003;van Eijk et al, 2008). An analysis of the 455 data sets from those studies supported the expectation of common timing parameters across tasks: The model including common timing parameters for all tasks was rejected in 24 (5.27%) of the occasions at the 5% significance level (see García-Pérez & Alcalá-Quintana, 2012b, 2015a, 2015b.…”
Section: Empirical Evidence Supporting the Modelmentioning
confidence: 84%
“…1 is simple and easily tractable mathematically, and it has often been used to model arrival latencies and peripheral processing times (e.g., Colonius & Diederich, 2011;Heath, 1984). In addition, this distribution has proven empirically adequate to account for observed performance in timing tasks (see García-Pérez & Alcalá-Quintana, 2012a, 2012b, 2015a, 2015b, 2015c. Thus, and without loss of generality, these are the distributions that will be used here.…”
Section: �68mentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, plausible models are expected to give a good fit to observations with a relatively small qopnamelog(trueL^). One can perform a likelihood-ratio-based test to evaluate goodness of fit to measurements, see e.g., García-Pérez and Alcalá-Quintana (2015a,b). The idea is to compare the purposed HM model and the saturated model (which contains parameters just being detection probabilities based on binomial fit at each amplitude) by the ratio of likelihood denoted by G 2 .…”
Section: Model Fitting and Evaluationmentioning
confidence: 99%